An observational feasibility study of a new anaesthesia drug storage tray. (3rd January 2018) - Almghairbi, D. S.; Sharp, L.; Griffiths, R.; Evley, R.; Gupta, S.; Moppett, I. K.
Summary: Drug errors in the anaesthetic domain remain a serious cause of iatrogenic harm. To help reduce this issue, we explored the potential safety impact of using a simple colour‐coded tray for anaesthetic drug preparation and storage. Over a six‐month period, three different trained researchers observed 30 cases at three NHS Trusts. Ten observations involved standard drug trays in 'normal' practice, and 20 observations, involved 'Rainbow trays' before and after their introduction. We conducted 20 semi‐structured interviews immediately after completing the Rainbow tray observation with the anaesthetists involved. All discussions and detailed notes taken were transcribed, qualitatively analysed using line‐by‐line coding and then synthesised into narrative themes. We found that using standard, single compartment trays enabled quick, cheap, and portable drug preparation and storage, but was linked to potential or actual harmful errors, such as syringe swaps. Rainbow trays were perceived to be easy to use and effective at all three sites, aiding drug identification and separation, and hence likely to reduce drug error and increase patient safety. We have demonstrated that it is feasible to introduce a new colour‐coded compartmentalised Rainbow drugs tray into clinical practice at three NHS hospitals in England. Further research is needed into their effect on the prevalence of drug error.